PENGARUH MODEL PROBLEM BASED LEARNING (PBL) DIKOMBINASIKAN PENDEKATAN LINGKUNGAN ALAM SEKITAR (PLAS) TERHADAP LITERASI SAINS DI UPTD SDN CIPUTAT 06 - Hidayti, Safitri; Azmi Al Bahij (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model combined with the Environmental Surroundings Approach (PLAS) on students’ science literacy. The research uses a quantitative method with a quasi-experimental design and a nonequivalent control group design. The sample consists of 61 students, with 30 students in the ekperimental group and 31 students in the control group. Data was collected through science literacy tests and observations. The data analysis using the t-test showed a significance value of 0.001, indicating a positive effect of the combination of PBL and PLAS on students’ science literacy. Thus, it can be concluded that the combination of PBL and PLAS is effective in improving student’s science literacy in school.